THE CONTRIBUTION OF EMPLOYEE COMMITMENT TO DUTY TO JOB SATISFACTION OF EMPLOYEES OF THE SOCIAL AND LABOR OFFICE OF THE CITY OF PADANG - Mardianti, Desi (Jurnal Manajemen Pendidikan, 2024)
Qualified human resources who can carry out work and produce something desired in accordance with organizational goals. Based on field observations, the symptoms seen show that employee job satisfaction at the Padang City Social and Manpower Office tends to be low. In this case, it is suspected that employee job satisfaction has something to do with the factors that influence job satisfaction itself. The symptoms that reflect low employee job satisfaction will have a negative impact on employee work productivity, and employee job satisfaction will not be realized. It is feared that this can affect the achievement of organizational goals. This study aims to reveal the contribution of employee commitment to duty to Employee Job Satisfaction. The method used is a descriptive correlational quantitative method. The results showed that: (1) Employee commitment to task contributes significantly to Employee Job Satisfaction by 15.1%, (2) Employee commitment to task together contributes to Employee Job Satisfaction by 19.4%. The analysis also shows that employee commitment to duty is in the sufficient category, as well as employee job satisfaction which is also in the sufficient category. The findings of this study have implications that employee job satisfaction can be improved through increasing employee commitment to duty.